How healthy are Manitoba’s Francophones? A summary of report, Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Ottawa, Manitoba Center for Health Policy, 2012)
A summary of the report, Health and Healthcare Utilization of Francophones in Manitoba / La santé et l’utilisation des services de santé des francophones du Manitoba by Mariette Chartier, Greg Finlayson, Heather Prior, Kari-Lynne McGowan, Hui Chen, Janelle de Rocquigny, Randy Walld, Michael Gousseau Summary written by Michelle Houlden

Quel est l’état de santé des francophones du Manitoba ? Sommaire du rapport intitulé La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, University of Manitoba, 2012)

Comparing the rates of mental disorders among different linguistic groups in a representative Canadian population - Vasiliadis, Helen-Maria; Lepnurm, Marje; Tempier, Raymond; Kovess-Masfety, Viviane (Social psychiatry and psychiatric epidemiology, 2012)
Purpose We aimed to determine whether linguistic group influences reported prevalence rates for a number of common mental disorders. Methods Secondary data analyses of the Canadian Community Health Survey cycle 1.2 (CCHS 1.2) were carried out on representative bilingual French and English, monolingual French and English and other language groups in Canada. Past year prevalence of major depression, anxiety disorders (agoraphobia, social phobia, panic disorder) and alcohol abuse/dependence were ascertained using versions of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI) questionnaire. Multivariate data analyses were used to model past year presence of a mental disorder as a function of linguistic group, defined as languages can converse in, and adjusting for socioeconomic, demographic and cultural factors. Results Overall, past year rates for the presence of a common mental disorder were 10.7% (9.7–11.7%) for the bilingual English; 9.0% (8.1–9.9%) for the bilingual French; 10.2% (9.8–10.6) for the monolingual English; 8.5% (7.7–9.3%) for the monolingual French; and 8.3% (6.1–10.4%) for the other language group. After adjusting for a number of socio-demographic, economic and cultural factors, the multivariate analyses showed that the linguistic groups were equally likely to report the presence of a past year common mental disorder. This was also true for comparisons between the bilingual participants responding in French and English. Conclusions The differences observed in the reported crude rates for the presence of mental disorders across the different linguistic groups in Canada were explained by socio-demographic, economic, and factors such as immigration, spoke a third language and province of residence, and not explained by language of interview.